Communication in Emergency Situations – the Covid 19 Pandemic in Foster Families. Organization and Principles of Operation - Walancik, Karolina (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The article contains the results of research on the organization and course of communication (contacts) in emergency situations, e.g., the COVID 19 pandemic (border closure, quarantine, social distance, epidemiological supervision). The conducted research concerned the contact of children in foster families in emergency situations with their natural parents with the use of electronic communication, which has been standardized by Polish law. The diversified involvement of natural parents in contacts as well as the low use of electronic communication means for contacts was indicated. The obtained research results make it possible to recommend the use of children in foster families in emergency situations with natural parents from electronic communication means in emergency situations, such as pandemics, epidemics, long-term separation in the vast majority of cases. Such solutions should be legally established as alternatives. The conducted research and analysis of results supplement the knowledge in the field of communication, education and organizational solutions for communication in emergency situations. The author, analyzing the common phenomenon of the effectiveness of contacts between natural parents and children staying in foster families in emergency situations, analyzed the involvement of the natural family and foster family from the perspective of emergency situations and the possibilities offered by electronic communication means.